Growth Poles : The Next Phase - World Bank (World Bank, Washington, DC, 2016)
This report looks at the growth poles policy in Romania to determine ways to increase its effectiveness and efficiency for the next programming cycle (2014-2020). The growth poles policy in Romania has been initiated in 2008, as a means to support a balanced economic development of the country, while still targeting investments to maximize economic impact. A total of seven growth poles have been designated and are currently supported as such, via an integrated development plan designed for each. In an effort respond to all the above the Romanian Ministry of Regional Development and Public Administration (MRDPA) has engaged with the World Bank in a broader advisory services partnership implemented between 2012-2013. The current review is a result of this joint work. The report is grouped into three main parts. The first part sets out the context of analysis, including a brief presentation of growth poles policy objectives as well as the European policy context, and conceptual debates in which it is framed. The second part includes a set of recommendations regarding the growth poles policy for the next programming cycle (2014-2020). The third part includes an analysis of each of the growth poles, presenting specific recommendations for each.